A novel ferroptosis phenotype‐related clinical‐molecular prognostic signature for hepatocellular carcinoma. Issue 14 (4th June 2021) - Deng, Tuo; Hu, Bingren; Jin, Chen; Tong, Yifan; Zhao, Jungang; Shi, Zhehao; Zhang, Tan; Deng, Liming; Sun, Zhifu; Chen, Gang; Wang, Yi
Abstract: Ferroptosis is a newly identified cell death mechanism and potential biomarker for hepatocellular carcinoma (HCC) therapy; however, its clinical relevance and underlying mechanism remain unclear. In this study, transcriptome and methylome data from 374 HCC cases were investigated for 41 ferroptosis‐related genes to identify ferroptosis activity‐associated subtypes. These subtypes were further investigated for associations with clinical and pathological variables, gene mutation landscapes, deregulated pathways and tumour microenvironmental immunity. A gene expression signature and predictive model were developed and validated using an additional 232 HCC cases from another independent cohort. Two distinct ferroptosis phenotypes (Ferroptosis‐H and Ferroptosis‐L) were identified according to ferroptosis gene expression and methylation in the patients with HCC. Patients with the Ferroptosis‐H had worse overall and disease‐specific survival, and the molecular subtypes were significantly associated with different clinical characteristics, mRNA expression patterns, tumour mutation profiles and microenvironmental immune status. Furthermore, a 15‐gene ferroptosis‐related prognostic model (FPM) for HCC was developed and validated which demonstrated accurate risk stratification ability. A nomogram included the FPM risk score, ECOG PS and hepatitis B status was developed for eventual clinical translation. Our results suggest that HCC subtypes defined by ferroptosis gene expression and methylation may be used to stratify patients for clinical decision‐making.